Analisis Sistem Koordinasi Proteksi Over Current Relay (Ocr) Dan Ground Fault Relay (Gfr) Tegangan 20 Kv Bay Trafo Pada Gardu Induk Sanga-Sanga Kalimantan Timur - Thaha, Sarma; Indrawan, Andi Wawan; Pongkiding, Yosua Januarius (Jurnal Teknologi Elekterika, 2022)
As a provider of electricity services, PLN is required to provide service and supply of electricity with good quality, continuity, improvement and efficiency. Disturbances in distribution systems are short circuit faults between phases or ground phase faults. To protect properly, proper coordination of relay settings is required. Among the equipment in the protection system used in distribution lines are overcurrent relays (OCR) and ground fault relays (GFR). In this study, an analysis of the OCR and GFR settings will be carried out on a 20 kV cubicle at the Sanga-Sanga Substation, East Kalimantan, with the help of the DigSILENT Power Factory 15.1.7 application with a disturbance simulation at 10% and 90% of the feeder length. Based on the analysis results, it is obtained that the short circuit results of 3 phases, 2 phases, and 1 phase to the ground have a value that is not much different from the calculation, while the OCR setting for the outgoing relay is 0.8 A on the secondary side. TMS is 0.083 seconds while the relay is on the incoming side of 20 kV 1 A and TMS of 0.198 seconds. The GFR setting for the outgoing relay is 0.06 A on the secondary side, and TMS is 0.1 seconds, and the relay on the incoming side is 20 kV 0.015 A and TMS is 0.26 seconds).